2011
DOI: 10.1016/j.mehy.2011.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Stimulants and growth in children with attention-deficit/hyperactivity disorder

Abstract: a b s t r a c tInitial suggestions that suppression of growth may be an intrinsic characteristic of attention-deficit/ hyperactivity disorder (ADHD) have now largely been disproven. Although controversy persists regarding the possible negative effect of adrenergic stimulants on growth in children with ADHD, the consensus that appears to be reached in the scientific literature is that stimulant usage may cause a manageable attenuation of growth in these children. Since it is known that stimulants increase the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 117 publications
0
8
0
Order By: Relevance
“…Other studies have found more mild and transient growth disruptions in ADHD children (Negrao & Viljoen 2011), and that even with stimulant treatment, associated growth deceleration and loss of expected height may amount to only a one to two centimeter deficit per year during treatment (Poulton, 2005, Drappatz et al, 2006. Comparison of paired height measurements, before and after ADHD treatment, suggest a height deficit of only about 1 cm/year during the first 1 to 3 years of ADHD treatment (Pliszka, 1998).…”
Section: Growth In Stimulant Medication Treated Adhd Childrenmentioning
confidence: 98%
See 4 more Smart Citations
“…Other studies have found more mild and transient growth disruptions in ADHD children (Negrao & Viljoen 2011), and that even with stimulant treatment, associated growth deceleration and loss of expected height may amount to only a one to two centimeter deficit per year during treatment (Poulton, 2005, Drappatz et al, 2006. Comparison of paired height measurements, before and after ADHD treatment, suggest a height deficit of only about 1 cm/year during the first 1 to 3 years of ADHD treatment (Pliszka, 1998).…”
Section: Growth In Stimulant Medication Treated Adhd Childrenmentioning
confidence: 98%
“…Reductions in height, weight and / or body mass index are commonly reported with stimulant therapy use for ADHD (Faraone et al, 2008, Negrao & Viljoen, 2011, and may be worse in larger children, those who are naive to therapy or who have a greater cumulative exposure to stimulants (Faraone et al, 2010). Ptacek et al found a lower percent body fat in medically treated ADHD males (age 4 -16 years) as compared to non-treated peers (Ptacek et al, 2009b).…”
Section: Growth In Stimulant Medication Treated Adhd Childrenmentioning
confidence: 99%
See 3 more Smart Citations